Induction of UPR Promotes Interferon Response to Inhibit PRRSV Replication via PKR and NF-κB Pathway - Zhu, Zhenbang; Liu, Panrao; Yuan, Lili; Lian, Zhengmin; Hu, Danhe; Yao, Xiaohui; Li, Xiangdong (Frontiers in Microbiology, 2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) was previously shown to induce a certain level of cellular stress during viral replication. Unfolded protein response (UPR) is a cellular stress response responsible for coping with stress and cellular survival. However, the pathway leading to the induction of UPR that may influence PRRSV replication is still unknown. Here, we found that PRRSV infection-induced UPR prior to interferon response. Induction of UPR significantly enhanced the expression of interferon and interferon-related genes, thus leading to the suppression of PRRSV infection. Next, we explored the underlying mechanisms of UPR-induced antiviral response. We found that induction of UPR promoted the expression of protein kinase R (PKR), and PKR was highly correlated with the reduction of PRRSV replication. Furthermore, tunicamycin stimulation and PKR overexpression activated NF-κB and interferon response at the early stage of PRRSV infection, thus reinforcing the expression of type I interferons and proinflammatory cytokines and leading to inhibition of PRRSV. In addition, PRRSV nsp4 was shown to reduce the expression of PKR. These findings might have implications for our understandings of the host's immune mechanism against PRRSV and a new strategy of PRRSV to evade the host antiviral immunity.